When Friends Become Foes: Strategies and Features of Arguing - Allycia Susanti (Warmadewa University, 2022)
This article will show that there are strategies and features present in arguing. This paper explores these aspects applying discourse analysis to the isolated data. The data are in the form of transcripts of arguing taken from the American TV Show Euphoria involving teenage characters with the exception of one adult character. They are then examined using conversational analysis and ethnographical analysis to explore that in addition to the intentions of arguing, background attributes of the conversation such as the participants’ age, region, and relationship with each other can affect the word choice, sentence content, and sentence structure that are utilised in arguing.